A leitura e a escrita como fundamento da prática pedagógica: a percepção de estudantes do curso de pedagogia da UFT/câmpus de Arraias-TO, - OLIVEIRA, Bianca Machado de (Universidade Federal do Tocantins, 2021)
At all educational levels, reading has become important. Therefore, reading should start long before the literacy period and continue through the different degrees of education, as it constitutes a form of interaction for people from any area of knowledge, as it allows man to situate himself with others, enables the acquisition of different points of view and broadening of experiences. This study aims to analyze the reading and writing experience of students in the Pedagogy course at the Federal University of Tocantins (UFT), in Arraias, observing a pedagogy class, investigating whether these students have the habit of reading and writing and to analyze which the difficulties encountered by them in relation to reading and writing. For this research, a bibliographic research was carried out to have a basis for the proposed theme, through books, internet research, articles, among others. It also included field research. The target audience participating in this experiment involved 23 students from the Pedagogy degree course, at the Federal University of Tocantins, Campus Arraias, being the first and the last expert. through this bibliographic and field study, that the difficulty that students have with reading and writing, often due to lack of interest or due to day-to-day fatigue, which in one way or another ends up contributing a lot as a factors in the there is a loss of interest in it.